مفتی سید محمد حسین نیلویؒ کے ترجمہ قرآن’’تبیین القرآن‘‘کےخصائص اورتفردات:تجزیاتی مطالعہ: Tabyīīn-ul-Qur’ān by Muftī ‘Sayyed Muḥammad Ḥusain Neelvī: Tabyeen :Distinctions, Characteristics and Tafarudāt:Aanalytical Study) - Dr. Abdul Ghafoor,; Dr.Hafiz Muhammad Zaheer, (MEI, 2023)
To make the Holy Quran understandable for general public, the sub۔continent scholars translated the holy Quran in various languages.Shah Abduul Qader Dehlavi made the first idiomatic translation of the Holy Quran in urdu language.It is considered as a reference in translations,as the translators after him used this translation in their translations.His brother Shah Rafiuddin translated the Holy Quran adopting word by word approach.These both translations of the Holy Quran are commonly used by the scholars of tafseer and Quranic studies. In the twentieth century ,scholars focused on idiomatic translations.Later on another type of translation of the Quran,the exegetical translations,was also adopated. Maulana Ashraf Ali thanvi rendered the tafseeri translation of the holy Quran.Using this third approach in the later half of the twentieth century ,Maulana Mufti Sayyed Muhammah Husain nilvi translated the complete Quran ,published and revised the translation of the Quran.The salient feature of the translation is this translation is a coherent translation of the entire Quran.The subjects of all the verses are linked togather.The translation of each verse is intergrated in the light of the context.This translation is the first fully integrated interpretation and commentary translation in Pakistan ,in which the Quranic teachings are clarified without adding parentheses in the translation itself. Maulana Mufti Sayyed Muhammah Husain nilvi also considered other exegetical translations while translating the verses of the Holy Quran. Moreover he also addressed the questions that arise in the translation of the Quran,the objections of opponents of Islam to the Holy Quran and Islam have been also addressed shortly.